PENERAPAN METODE ANALISIS VARIANS KECEPATAN MAKAN TERHADAP PANAS PEMOTONGAN PADA MESIN FREIS KUNZMANN UF6N - Fadli Babunga; Fentje Abdul Rauf; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
The goal of this research is related to findng the relationship between feeding rate against cutting rising temperature at machining process using analysis of varience. The result showed that the greater of feeding rate, the higher heat produced in milling proses prom variance analisis at 95% confident level the increase of feeding rate will significant affect cetting temperature both at chips, cotting tools and working materials. Keywords : feeding rate,cetting temperature,maching.